2018
DOI: 10.3390/geosciences8120450
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Flood Modeling Challenges in Defended Urban Backshores

Abstract: Coastal flooding is a significant and increasing hazard. There are multiple drivers including rising coastal water levels, more intense hydrologic inputs, shoaling groundwater and urbanization. Accurate coastal flood event prediction poses numerous challenges: representing boundary conditions, depicting terrain and hydraulic infrastructure, integrating spatially and temporally variable overtopping flows, routing overland flows and incorporating hydrologic signals. Tremendous advances in geospatial data quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 192 publications
(358 reference statements)
0
33
0
Order By: Relevance
“…Thus, special attention is required for topographic data because a robust flood model needs high vertical accuracy linked to a geodetic reference system, since in many cases, flood-prone areas are found in marginal regions of low-slope floodplain and may embrace large areas, such as this case study (Uruguay River basin, Itaqui) (Gupta, 2009;Mistry, 2009). The modeling of a flood hazard map is linked to the local geodetic reference system, corroborated with the identification and monitoring of flood situations, and construction of realistic predictive scenarios (operational level) for risk management and adaptation (governmental agencies, such as the local civil defense) (Joshi et al, 2012;Gallien et al, 2018;Jongman, 2018). It is extremely important to do the calibration of the digital elevation model (DEM) using high-accuracy ground control point (GCP) data, aimed at improving the vertical accuracy, and applied to regional or local studies about floods (Araújo et al, 2018).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, special attention is required for topographic data because a robust flood model needs high vertical accuracy linked to a geodetic reference system, since in many cases, flood-prone areas are found in marginal regions of low-slope floodplain and may embrace large areas, such as this case study (Uruguay River basin, Itaqui) (Gupta, 2009;Mistry, 2009). The modeling of a flood hazard map is linked to the local geodetic reference system, corroborated with the identification and monitoring of flood situations, and construction of realistic predictive scenarios (operational level) for risk management and adaptation (governmental agencies, such as the local civil defense) (Joshi et al, 2012;Gallien et al, 2018;Jongman, 2018). It is extremely important to do the calibration of the digital elevation model (DEM) using high-accuracy ground control point (GCP) data, aimed at improving the vertical accuracy, and applied to regional or local studies about floods (Araújo et al, 2018).…”
mentioning
confidence: 67%
“…To evaluate and calibrate the DEM of the study area, a matrix was constructed with the orthometric height values of control points and the SRTM image. This dataset was subjected to linear regression analysis, with ground control point values as a dependent variable and SRTM data as an independent variable, which is a common procedure found in the literature for DEM calibration (e.g., Gorokhovich and Voustianiouk, 2006;Forkuor and Maathuis, 2012). Then, the DEM obtained from the SRTM image was calibrated using the model proposed by the linear regression.…”
Section: Digital Elevation Model (Dem) Calibrationmentioning
confidence: 99%
“…First, the storm event of 6 December 2010 was simulated with XBeach, with boundary conditions extracted from WW3 (same domain and grid as the validation) ( A hypothetical storm scenario for the year of 2100 was simulated based on an increase in sea level only, assuming a stable future wave climate. The observed rate of sea level rise is both the result of eustatic sea level variations and regional glacio-isostatic adjustments (GIA) along Atlantic Canada [5,[42][43][44], varying between −1 and −4 mm/year in the Gulf of St Lawrence [5,45]. The relative sea level has risen at a mean rate of 0.93 ± 1.25 mm/ year over the past ~1500 years in the Chaleur Bay and GIA was a significant contributor to this rate [79].…”
Section: Actual and Future Design Storm Simulationsmentioning
confidence: 99%
“…Gallien et al [42] further demonstrated that drainage can reduce flood propagation. Multiple flooding pathways can also influence the flood extents [45,46]. Urbanization in coastal areas greatly affects the beach response to, and recovery from, storm events [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation